Mechanism of action of the erector spinae plane block: distribution of dye in a porcine model. Issue 3 (6th January 2020) - Otero, Pablo E; Fuensalida, Santiago E; Russo, Pedro C; Verdier, Natali; Blanco, Carlos; Portela, Diego A
Abstract : This study aimed to describe the anatomical distribution of dye injected in the erector spinae plane (ESP) in a porcine living model, which could aid to reveal factors potentially relevant to the unexplained clinical effects of the ESP block. Six pigs received 0.6 mL/kg of 0.25% new methylene blue at the level of the sixth thoracic vertebra through either a cranial-to-caudal or a caudal-to-cranial in-plane ultrasound-guided bilateral ESP injection 20 min before euthanasia. Spread of dye evaluated through transverse cryosections (four injections) extended from T5 to T10 and from T5 to T8 when a cranial-to-caudal direction of injection was used, and from T5 to T9 and from T5 to T8 when the opposite direction of injection was used. A median of 4.5 medial and lateral branches of the dorsal rami was observed stained through anatomical dissection (eight injections), regardless of the direction of injection. No evidence of dye was found in the thoracic paravertebral or epidural spaces, where the dorsal root ganglia, ventral rami and rami communicantes are located. In all the cases, dye solution was found in the prevertebral thoracic lymph nodes. In this study, ESP injection resulted in a median spread over five spinal segments (12 injections), staining the lateral and medial branches of the dorsal rami of the spinal nerves, regardless of the direction of the needle used.